Transforming the Role of Islamic Education Teachers: A Study of Learning Resources in the Digital Era, Analysis of 21st Century Skills - Warih Bagaskara Putri Afriansyah; Najwa Chikmiah; Moh. Faizin (al-Afkar, Journal For Islamic Studies, 2026)
This study examines the changing role of Islamic Religious Education (PAI) teachers in the digital era, particularly in terms of how they manage learning resources and the skills needed for teaching in the 21st century. The research method used is library research with a qualitative approach. The groups studied include various types of scientific writings, such as national journals and indexed academic books, and the data collection method involves observation and analysis of the contents of these sources. This study shows that the role of Islamic Religious Education (PAI) teachers has changed from being the main source of information where the teacher is in the middle (Teacher Centered), to being more flexible as a director who supports student-centered learning (Student Centered) and is able to keep up with new technological developments. Using digital learning tools such as e-books, video lessons, and digital platforms can help students be more motivated in learning and improve their ability to learn independently. In addition, 21st-century skills such as understanding how to use digital tools, being proficient in using technology with the TPACK method, and having the 4C abilities of critical thinking, creativity, collaboration, and communication, are very important to improve the effectiveness of PAI learning. However, several challenges remain, such as differences in people's ability to access technology, doubts about the accuracy of religious information, and a lack of available support facilities. Teachers must continually improve their skills to maximize the use of Islamic Religious Education (PAI) lessons in today's digital world.